PENGEMBANGAN MEDIA PEMBELAJARAN TITIK GARIS BIDANG (TGB) UNTUK SISWA TUNAGRAHITA RINGAN KELAS VIII SMPLB - Linda Ardani Afriliziana; Maimunah Maimunah; Susda Heleni (Prodi Pendidikan Matematika FKIP Universitas Madura, 2020)
The purpose of the research conducted is to produce math learning media field line and point (TGB) on the material of cuboid and cube for mild intellectual disability 8th in SMPLB Pekanbaru. The developed media learning are TGB method and manual book. The research methods Borg and Gall development models with ten stages: (1) Potential and problems; (2) Collect information; (3) Product design; (4) Design validation: (5) design revisions; (6) Product testing; (7) Product revisions; (8) Usage testing; (9) Product revisions; and (10) mass production. This research is conducted until product testing stage, due to the Covid-19 pandemic it is hard to continue the research from 7th to 10th stages. Apparantly it needs wider coverage and more sufficient term on making this research works fully at times like this. The results of the data validation analysis show the average assessment for the learning media and the manual book is 2.77 with valid criteria. The results of the analysis of the practical data were collected from the results of the students response to the media, with average percentage of 100%. Based on the results of data analysis and discussion can be concluded that the mathematics learning media developed has fulfilled valid criteria that is worthy to be used and practical that is easy to use.